Tripwire - Child, Lee. (New York : Jove Books, 2005)
Former military policeman Major Jack Reacher goes to the rescue of a 30-year-old woman lawyer he last saw when she was 15. She is the daughter of Reacher's late commanding officer and some nasty land swindlers want her dead. By the author of Die Trying.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Vietnam War, 1961-1975 -- Missing in action -- Fiction; Private investigators -- Florida -- Key West -- Fiction; Detective and mystery stories, American; Key West (Fla.) -- Fiction